Assessment of Antibiotic Prescription Practices in a Tertiary Care Hospital - Selvaraj R (Journal of Clinical and Biomedical Sciences)
Background: Widespread and irrational use of antibiotics has caused microbials to acquire re-sistance and is an important public health problem to be urgently addressed. Hence there is a need to con-stantly monitor the prescription practices through audits and to initiate corrective measures. Objectives: To asses the antibiotic prescription practice in a teaching hospital. Materials and Methods : The prescrip-tions originating from medicine out patient department on one day in a week for five months were assessed for appropriateness in dosage, duration of treatment and use of fixed dose combination drugs (FDCs). The clinical diagnosis and patients details were recorded in a structured proforma. Results: Out of 650 patient prescription studied 180 patients (27.6%) received antibiotics. Among them 25.3% patients were pre-scribed one antibiotic and (18.8%) were prescribed antimicrobial FDCs. Out of the 180 prescriptions, 47% were irrational. The most commonly prescribed antibiotic categories were β-lactam antibiotics (35.1%), followed by fluoroquinolones (18.8%) and combinations of antibiotics from different groups (13.8%). Con-clusion: Higher frequency of irrational antimicrobial prescriptions suggests that antibiotic restriction poli-cies and a multidisciplinary effort to reduce usage are urgently required. Keywords: prescription practice, antibiotics, FDCs